2021
DOI: 10.2147/ccid.s325166
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire and Lactic Acid Sting Test Play Different Role on the Assessment of Sensitive Skin: A Cross-sectional Study

Abstract: Background Questionnaires and lactic acid sting test (LAST) are two widely used methods to identify sensitive skin. However, the self-perceived sensitive skin by questionnaires was not consistent with the determination of LAST. Objective The aim of the study was to measure the biophysical properties noninvasively of sensitive skin evaluated by questionnaire and LAST and to investigate their correlations with the scores of questionnaire and LAST. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“… 17 , 22–30 Among them, it was found that Chinese females subjected to semisubjective tests (LAST/CAT) showed higher TEWL values on the cheek. Additionally, ten studies showed no difference in the values on the cheek, 33 , 35 face, 27 , 28 , 37 , 38 , 40 forearm, 34 , 36 , 37 body 34 , 35 or hand. 39 …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“… 17 , 22–30 Among them, it was found that Chinese females subjected to semisubjective tests (LAST/CAT) showed higher TEWL values on the cheek. Additionally, ten studies showed no difference in the values on the cheek, 33 , 35 face, 27 , 28 , 37 , 38 , 40 forearm, 34 , 36 , 37 body 34 , 35 or hand. 39 …”
Section: Resultsmentioning
confidence: 98%
“… 22 , 23 , 25–33 , 36 , 38–43 , 45 In cross-sectional and cohort studies, a wide range of skin capacitance values was reported (16.7–80.3 AU). 23 , 25 , 26 , 28 , 29 , 32 , 33 , 36 , 40–43 Among the case–control studies, four articles clearly reported lower SCH values in subjects with SS or stingers at different facial sites (forehead, cheek, nasolabial fold, and chin). 22 , 27 , 30 , 45 Of these, two studies used questionnaires, 22 , 30 one used LAST, 45 and one used both questionnaires and LAST.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…While our technique for measuring the moisturizing effect is first described and applied here, the lactic acid sting test (LAST), which also measures capacitance using a Corneometer (similarly to our dermatoscope's Corneometer) is highly comparable to it [11]- [13].…”
Section: Skin Hydrationmentioning
confidence: 99%